The System Model of Self-realization of the Personality - S I Kudinov; A I Krupnov (Peoples' Friendship University of Russia (RUDN University), 2008)
In the article the basic theoretical approaches of research of self-realization of the person are analyzed. Their critical analysis is given and the author's conceptual model is offered within the framework of the system approach where for the first time the forms, kinds and structure of the given phenomenon are allocated.